On Farm Evaluation of Eucalyptus globulus Labill Leaf and Chenopodium ambrosioides L. Whole Plant Powder against Storage Insect Pests in Stored Maize at Sokoru District in Jimma Zone of Oromia Regional State, Ethiopia - Lelise Tilahun Dufera; Abebe Yimer Tadesse; Waktole Sori Gobena; Chala Gowe Kuyu (Psyche: A Journal of Entomology)
Maize is the second most widely grown cereal and gaining importance as a highly nutritious crop in Ethiopia. However, it is severely destroyed by storage insect pests and needs further research to minimize losses. In line with this, research was initiated to evaluate the efficacy of two botanical plant powders (Eucalyptus globulus Labill leaf and Chenopodium ambrosioides L. whole plant) against storage insect pests of maize grains of two maize varieties (BH-661 and Limu) in polypropylene sacks storage conditions at Jimma Zone, Sokoru district. The plant powders were compared with untreated control, and completely randomized design was used in the experiment with three replications for each treatment. Germination capacity, thousand grain weights, percent of insect damage, and weight loss of the stored grains were evaluated and reported in the range of 69.67–94.33%, 318.7–339.3 g, 3.67–50%, and 0.2843–5.22%, respectively, after five months of storage for grains treated with botanicals. However, germination capacity of 10% and 65.33%, percent insect damage of 80.33% and 48%, and weight loss of 23.53% and 5.89% were observed for BH-661 and Limu varieties, respectively, after five months of storage for untreated control. The result indicated that both tested botanicals were effective in protecting the storage insect pests and maintaining the quality of the grains tested in comparison with control and Chenopodium ambrosioides L. whole plant powder is more effective. Although there was significant protective effect compared to untreated control, their effectiveness was decreased drastically after five and three months of storage for Chenopodium ambrosioides L. whole plant powder and Eucalyptus globulus Labill leaf powder, respectively. It is recommended that further research should be done to check if the increasing rate of application increases protection duration of these botanicals and the toxicity of Chenopodium ambrosioides L. should be further studied to use it as a storage insect protectant of maize grains intended for food purpose.